Viscosity approximation methods with Meir-Keeler contractions for nonexpansive semigroups - Suthep Suantai (2018)
We establish strong convergence theorems of the viscosity approximation method associated with Meir-Keeler contractions for nonexpansive semigroups in a real Hilbert space. The main results improve and extend the corresponding results existed in the literature. © 2012 by the Mathematical Association of Thailand.